Impaired response inhibition to negative emotional stimuli in depressed adolescents with non-suicidal self-injury: a neurophysiological perspective - Zhao, Lin; Hong, Su; Peng, Xinyu; He, Xiaoqing; Hu, Jinhui; Ma, Lingli; Liu, Xinyi; Tao, Wanqing; Chen, Ran; Jiang, Zhenghao; Zhang, Chenyu; Liao, Jing; et al. (Frontiers in Psychiatry, 2025)
BackgroundNon-suicidal self-injury (NSSI) is an increasingly recognized clinical and public health issue among adolescents. This behavior exhibits certain addictive characteristics, leading it to be classified as a behavioral addiction. Response inhibition is believed to play a role in the occurrence of addictive behaviors and is often impaired in the context of negative emotional states. In this study, we compared the behavioral performance, ERP time-domain and time-frequency characteristics among depressed adolescents with NSSI, depressed adolescents, and healthy controls when exposed to negative emotional stimuli. The aim was to investigate the impact of negative emotional stimuli on the response inhibition in depressed adolescents with NSSI, clarify the role of response inhibition in NSSI behaviors, and provide neurophysiological evidence for its underlying mechanisms.MethodsSeventy-one depressed adolescents with NSSI (MDD+NSSI group: 12 males, 59 females; mean age: 14.37 years), 55 depressed adolescents (MDD group: 24 males, 31 females; mean age: 15.29 years) and 25 healthy subjects (HC group, 13 males, 12 females, mean age: 15.72 years) were recruited to perform a two-choice oddball task related to negative emotional cues. All participants completed a self-administered questionnaire to gather demographic information. A trained psychiatrist administered the Hamilton Depression Scale (HAMD-17) to assess depression severity and used the Ottawa Self-Injury Inventory (OSI) to assess self-injury. Multichannel EEG was recorded continuously from 64 scalp electrodes using the Curry 8 system. EEG signal preprocessing and analysis was performed offline using the EEGLAB toolbox in MATLAB. The ERP time-domain features related to response inhibition were extracted from the difference waves, converted to the time-frequency features using the short-time Fourier transform (STFT), and the time-frequency values of the region of interest (ROI) were extracted and statistically analyzed.ResultsUnder exposure to negative emotional stimuli, depressed adolescents with NSSI exhibited significantly larger P300 amplitudes compared to both depressed adolescents and healthy controls. Moreover, depressed adolescents with NSSI showed significant event-related synchronization (ERS) in the Delta and Theta bands of FCz electrode from 0 to 0.6 seconds, and event-related desynchronization (ERD) in the Theta and Alpha bands of Pz electrode from 0.2 to 1.2 seconds, collectively reflecting functional processes associated with response inhibition.ConclusionsDepressed adolescents with NSSI showed increased P3d amplitudes, enhanced Delta/Theta ERS, and heightened Theta/Alpha ERD when receiving negative emotional stimuli, suggesting that depressed adolescents with NSSI have impaired response inhibition, which may contribute to the development of NSSI.